Secondary School Students' Preferences for STEM Subjects as University Study Options - Paudel, Krishna Chandra; Khanal, Khageshyor (Journal of Science and Technology, 2023)
Choosing a university course is an important and difficult decision for secondary level students, influencing their future careers and personal development. This study investigates the secondary level students’ preferences of course selection for their future university study option. The quantitative research method was adopted; a survey of 150 science students of grades XI and XII in Kathmandu, Nepal was carried out to study the personal interests to opt higher study. The study revealed that, STEM disciplines are popular among students, with 82% interest at least one within the first three preference but only 30% of the respondents preferred it as first option. Significant gender differences were seen, with male students favoring STEM (except health science) and female students preferring non-STEM courses. The research highlights the need for targeted actions to promote STEM education, particularly among female students, and recommends gender-inclusive career advice services, early STEM exposure, and diversified career exploration that could result in a more balanced distribution of career aspirations.